IMMIGRATION, OTHERNESS, ECONOMIC MOBILITY AND SOCIAL INCLUSION IN THE HOMELAND - Gloria Mayen Umukoro; Veronica Ebi Odey; Mamina Mba Ndifon (Universitas Negeri Makassar, 2021)
This research focuses on the impact of migration on the Cultural identity of Francophones in the diaspora. It explores the fascinating role of Culture and identity in national and regional integration. Examining the experiences of francophone immigrants from the diaspora, the study shows how ‘otherness’ affects immigrants’ capability to self-assert and adapt to reclaim their Africaness in the homeland. Two sets of immigrants are presented; the forced immigrant (Slavery), with a forced culture and the liberal immigrant, with liberal culture. Drawing from interviews, and individual experiences, the study emphasises the role of the immigrant, the community and the institutions in successful cultural integration in the homeland.